2016
DOI: 10.1371/journal.pone.0154101
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and Molecular Characterization of Miltefosine Resistance in Leishmania infantum Strains with Either Natural or Acquired Resistance through Experimental Selection of Intracellular Amastigotes

Abstract: During the last decade miltefosine (MIL) has been used as first-line treatment for visceral leishmaniasis in endemic areas with antimonial resistance, but a decline in clinical effectiveness is now being reported. While only two MIL-resistant Leishmania infantum strains from HIV co-infected patients have been documented, phenotypic MIL-resistance for L. donovani has not yet been identified in the laboratory. Hence, a better understanding of the factors contributing to increased MIL-treatment failure is necessa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
114
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(119 citation statements)
references
References 45 publications
(85 reference statements)
1
114
1
3
Order By: Relevance
“…Recently, Mondelaers et al . have also shown lower expression of LiMT in MIL‐resistant Leishmania infantum parasites but did not find any change in LiRos3 expression compared to that of sensitive parasites indicating that Milt resistant is independent of LiMT expression in these isolates. Although there were reports as above indicating different genes that trigger resistance, there was not a definite target studied to overcome the miltefoisne resistance.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Recently, Mondelaers et al . have also shown lower expression of LiMT in MIL‐resistant Leishmania infantum parasites but did not find any change in LiRos3 expression compared to that of sensitive parasites indicating that Milt resistant is independent of LiMT expression in these isolates. Although there were reports as above indicating different genes that trigger resistance, there was not a definite target studied to overcome the miltefoisne resistance.…”
Section: Discussionmentioning
confidence: 88%
“…The factors dwindling the expression levels of P-type ATPase, LdMT-LdRos3-dependent flippase activity in translocation machinery [18,19,29], and genes involved in neutralization of oxidative stress [28,[46][47][48][49] generate Milt-resistant parasites. Recently, Mondelaers et al [50] have also shown lower expression of LiMT in MIL-resistant Leishmania infantum parasites but did not find any change in LiRos3 expression compared to that of sensitive parasites indicating that Milt resistant is independent of LiMT expression in these isolates. Although there were reports as above indicating different genes that trigger resistance, there was not a definite target studied to overcome the miltefoisne resistance.…”
Section: Resistant Parasites Transfected With Pegfp-asfesodamentioning
confidence: 95%
“…An average of 50-fold genome coverage was obtained for both the wild-type and the mutant. Read depth coverage analysis did not identify specific gene amplification or deletion in the mutant (S1 Dataset), although aneuploidy was observed for 6 chromosomes (S1 Table), a phenomenon often observed in drug resistant mutants [18, 3739]. A search for point mutations revealed 18 homozygous single nucleotide polymorphisms (SNPs) in the AmB1000.1 mutant (S2 Table), 3 of which occurred within coding sequences (CDS) and caused an amino acid change (S2 Dataset).…”
Section: Resultsmentioning
confidence: 99%
“…donovani AmB-resistant promastigotes analysed by gas chromatography coupled to mass spectrometry (GC-MS) revealed an enrichment in cholesta-5,7,24-trien-3 β -ol [11], which suggests a more fluid cellular surface. On the other hand, resistance to MF primarily implies a transport defect with inactivation of the P-type ATPase miltefosine transporter (MT), or of its regulatory subunit LdRos3, causing a decrease in the uptake of lyso -phospholipids [1618]. A recent study has reported changes to the metabolism of lipids in L .…”
Section: Introductionmentioning
confidence: 99%
“…Resistance of Leishmania spp. to antileishmanial drugs is related to some extent to metabolic pathways, including glucose and thiol metabolism, the overexpression of certain enzymes, and increased membrane fluidity, resulting in altered interactions with antileishmanial drugs (Ghosh et al, ; Mondelaers et al, ; Vacchina, Norris‐Mullins, Carlson, & Morales, ). These biochemical and biophysical changes must be taken into consideration while investigating potential novel therapeutic strategies for the treatment of leishmaniasis.…”
Section: Molecular Targets For the Chemotherapy Of Malaria Leishmanimentioning
confidence: 99%